(untitled) (New York, 1986)
Is the first book to explore the ethnic derivations of American buildings with such a broad scope. The contributions of 22 groups are highlighted in this fascinating overview that provides an important new way of looking at the buildings that surround us. Groups covered include Native Americans, African-Americans, Belgians, Germans, Mexicans, the Irish and Japanese, among others.
Keywords: Ethnic architecture,Vernacular architecture,Kiến trúc dân tộc,Kiến trúc bản địa; United States,United States,Hoa Kỳ,Hoa Kỳ